2022
DOI: 10.47626/2237-6089-2021-0316
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mindfulness on suicidal behavior: a systematic review

Abstract: Introduction Mindfulness-based interventions (MBI) have been growing progressively as treatment options in the field of mental health. Aim: To assess the impact of mindfulness-based interventions for reducing suicidal thoughts and behaviors. Methods A systematic review was performed in December 2020 using PubMed, PsycINFO, EMBASE, SciELO, Pepsic, and LILACS databases with no year restrictions. The search strategy included the terms (‘mindfulness’ OR ‘mindfulness-based’)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…A systematic review was done in December 2020 to check whether meditation affects suicidal thoughts and behavior. A total of 14 studies were included from various databases, and all of them showed a reduction in suicidal behavior and ideas, especially those who had major depressive disorder [ 19 ].…”
Section: Reviewmentioning
confidence: 99%
“…A systematic review was done in December 2020 to check whether meditation affects suicidal thoughts and behavior. A total of 14 studies were included from various databases, and all of them showed a reduction in suicidal behavior and ideas, especially those who had major depressive disorder [ 19 ].…”
Section: Reviewmentioning
confidence: 99%
“…That is, to be considered a suicide prevention strategy, there is a prerequisite that it should conform to an evidence-based approach [9] . In this context, there is a recent systematic review that found that mindfulness-based intervention, a CAM modality, may contribute to the reduction of suicidal behavior [17] . However, there are no studies that comprehensively investigated the role of acupuncture on suicide prevention.…”
Section: Introductionmentioning
confidence: 99%